Institutional Frictions and Technological Unemployment - Hansen, Alvin H. (Quarterly Journal of Economics, 1931)
I. The argument that labor-saving improvements release purchasing power and so reabsorb displaced labor, 684.— The fallacy in this argument, 686.— Circumstances under which the displaced labor will be reabsorbed, 687.— II. Effect of price reduction, 688; of restrictions upon credit and wage rates, 690.— III. Effect of price maintenance, 692; of lower interest rates, 693.— IV. The effect of universal monopoly upon unemployment, 696.— Quasi-monopoly control of prices contrasted with rigid control of wage-rates, 697.